Peran Orang Tua dalam Penggunaan Gadget Anak Usia Dini - Ima Siti Rahmawati; Risbon Sianturi; Taopik Rahman (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
The rapid advancement of digital technology has significantly increased the frequency of device usage among early childhood. While digital devices have the potential to serve as instructional tools, the risk of negative impacts remains substantial without proper control. This literature study examines the critical importance of parental roles as technology mediators for children. Research findings indicate that active supervision, duration regulation, and the curation of educational content by parents are determinant factors. Through structured parental guidance, digital devices can be optimized to support various aspects of a child's development comprehensively